La Grande Guerre: The First World War in the journalism of French veterans. (18th May 2016) - Carlton, Sally
Abstract : Hundreds of veterans' organisations were established in France in the years following the First World War to provide members with companionship, information and assistance. Organisational newspapers proved central to these aims as a means of sharing stories and distributing practical advice. Despite the heterogeneity of the veterans' "movement", the narrative through which veterans' organisations referred to the experience of the First World War was singularly consistent. Not only was a particular narrative developed across the different veterans' groups, however; it has also been retained in the journalism of veterans of later wars. Analysing material produced in the newspapers of five key French veterans' organisations, this article firstly considers the narrative of the First World War veterans and probes the reasons for its development. It secondly considers the reasons why this narrative has been appropriated by veteran-journalists of later wars, concluding that the pre-eminence of the First World War in the French historical consciousness made it difficult for later veterans to develop an independent narrative, but also that the original narrative has helped successive generations of French veterans come to terms with the trauma of their own war experiences.